Correction: des Tombe, B., et al. Estimation of Temperature and Associated Uncertainty from Fiber-Optic Raman-Spectrum Distributed Temperature Sensing. Sensors 2020, 20, 2235 - des Tombe, Bas; Schilperoort, Bart; Bakker, Mark (Sensors (Basel, Switzerland), 2021)
The authors wish to make the following two corrections to this paper [...]